Strategic Insights into Integrating Accessibility in Software Development: Motivations, Barriers, Commitments, and Business Value - da Silveira, Luís André; Aljeedani, Wajdi; Medeiros Eler, Marcelo (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The widespread absence of accessibility in software applications prompted researchers to explore how organizations address accessibility in the software development process. Previous studies predominantly surveyed professionals engaged in daily development activities, revealing that barriers to accessible development are often associated with inadequate organizational support and commitment. Many organizations appear to undervalue accessibility as a quality factor that could confer business advantages, leading to insufficient resource allocation. Conversely, some organizations are recognized for their substantial investments in developing accessible software. In this scenario, this research aims to unveil strategic motivations, commitments, barriers, and benefits of considering accessibility in the development process, offering insights that can inspire other organizations, practitioners, and researchers to recognize the business value of accessibility. Accordingly, we interviewed 15 professionals that plays middle and high management roles in organizations that invest and have specialized teams to the delivery of accessible digital products and services. Our findings indicate that organizations delivering accessible products typically have robust executive support and dedicated policies. Despite challenges, these organizations ensure accessibility across the entire development process. Furthermore, they recognize numerous business benefits but emphasize ethical responsibility and inclusivity as paramount achievements.